3D Printed Materials in Water Treatment Applications. (29th December 2021) - Ghosal, Pranjal; Gupta, Bramha; Ambekar, Rushikesh S.; Rahman, Muhammad M.; Ajayan, Pulickel M.; Aich, Nirupam; Gupta, Ashok Kumar; Tiwary, Chandra Sekhar
Abstract: Water is one of the basic needs and vital concerns for human beings. As the world's population increases, our water resources become significantly stressed, not in terms of volume of water, but in terms of quality. Therefore, various water treatment processes such as filtration, adsorption, photocatalysis, and electrolysis are utilized based on the nature of contaminants present in water. 3D printing (3DP) manifests divergent development in different industries and scholastic research. Professionals from various sectors are utilizing the 3DP technique over conventional ones because it is more affordable, user‐friendly, and capable to manufacture complex structures rapidly with minimum wastage. This review summarizes the potential evolution, important outcomes of relevant research work, and future perspectives along with suggestions regarding the function of 3D printed material for water treatment applications. It is observed that a 3D printed spacer with modified geometry shows better antifouling ability than conventional ones. Furthermore, 3D printed materials with tunable properties such as surface area, thickness, and roughness enhance the removal efficiency for heavy metals, oil, and organic matter from water compared to standard treatment techniques. Abstract : The review covers the key findings, potential outcomes, and future prospects from relevant research works, as well as suggestions regarding the function of 3D printed materials in water treatment applications.